Expression of immunoglobulin G in human proximal tubular epithelial cells - Deng, Zhenling (Mol Med Rep, 2021)
Proximal tubular epithelial cells (PTECs) have innate immune characteristics, and produce proinflammatory factors, chemokines and complement components that drive epithelial-mesenchymal transition (EMT). Our previous studies revealed that human mesangial cells and podocytes were able to synthesize and secrete immunoglobulin (Ig)A and IgG, respectively. The aim of the present study was to evaluate the expression of Igs in PTECs. Firstly, IgG was detected in the cytoplasm, the cell membrane and the lumen of PTECs in the normal renal cortex by immunohistochemistry. Secondly, Igγ gene transcription and V(D)J recombination were detected in single PTECs by nested PCR and Sanger sequencing. Thirdly, Igγ, Igκ and Igλ were clearly detected in an immortalized PTEC line (HK-2) by immunostaining and western blotting, in which RP215 (an antibody that predominantly binds to non-B cell-derived IgG) was used. In addition, Igγ, Igκ and Igλ gene transcripts, conservative V(D)J recombination in the Igγ variable region, recombination activating gene 1/2 and activation-induced cytidine deaminase were all detected in HK-2 cells. These data suggested that PTECs may express IgG in a similar manner to B cells. Furthermore, IgG expression was upregulated by TGF-β1 and may be involved in EMT.